FACTORS AFFECTING THE FUNCTIONAL OUTCOME OF OXFORD PHASE 3 UNICOMPARTMENTAL KNEE ARTHROPLASTY - POLAT,AYŞE ESIN (2020)
ABSTRACT Objective: To determine the factors that affect the functional outcome of Oxford Phase 3 unicompartmental knee arthroplasty (UKA). Methods: We assessed a total of 52 UKA knees of 49 patients with a minimum follow-up of 2 years (24-72 months). We recorded the results for Range of motion (ROM) and body mass index (BMI) and the presence o patello-femoral arthrosis (PFA). In the radiological evaluation, we measured the posterior tibial slope (PTS), the tibial plateau angle (TPA) and the femorotibial angle, in addition to an assement using the Oxford radiological criteria. Patients were grouped by age, follow-up time, BMI, radiological criteria, PFA presence, occurance of complications and revision surgery. The clinical and functional results of these groups were compared statistically. Results: A total of 40 women and 9 men participated in the study, with an average age of 60 years, and a mean BMI of 34.6. No significant differences were found among the age and PFA groups. Postop VAS scores were high and knee evaluation scores were significantly lower in the morbidly obese group and in the groups with postop TPA <85º and >90º. The revision ratio was 11.5%. Conclusion: Postop TPA, PTS and morbid obesity are the most significant factors that can lead to revision surgery. Level of Evidence IV, Case series.